SMART DISINFECTION AND SANITATION TUNNEL (Spectrum Journal of Innovation, Reforms and Development, 2022)
The Smart Disinfection and Sanitation Tunnel is a demonstration of how It has been designed to provide maximum protection to people passing through the tunnel in around 15 seconds. Which can help the community to fight against the COVID-19.